Uji Aktivitas Afrodisiaka Sediaan Tablet Effervescent Ekstrak Kombinasi Buah Pare (Momordica Charantia L.) Dan Bawang Putih (Allium Sativum L.) Pada Mencit Putih Jantan (Mus Musculus L.) - Listina, Osie; Nurhidayati, Lailiana Garna; Fia, Nela Selfi Nur Okta (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Aphrodisiacs are substances derived from food or medicine that can enhance sexual desire. This study aimed to evaluate the aphrodisiac activity of effervescent tablet formulations containing extracts of bitter melon (Momordica charantia L.) and garlic (Allium sativum L.), both individually and in combination, in male white mice (Mus musculus L.). The ICC method (Introduction, Climbing, Coitus) was applied to 25 male Wistar mice divided into five groups. Group I served as the negative control and received distilled water orally. Group II was administered an effervescent tablet solution containing bitter melon extract at a single dose of 980 mg/kg BW. Group III received an effervescent tablet solution containing garlic extract at a single dose of 150 mg/kg BW. Group IV was given a combination effervescent tablet solution at a ½:½ ratio (bitter melon extract 490 mg/kg BW and garlic extract 75 mg/kg BW). Group V received a combination effervescent tablet solution at a 1:1 ratio (bitter melon extract 980 mg/kg BW and garlic extract 150 mg/kg BW). Observations were conducted for 2 hours, recording the frequency of ICC behaviors. Data were analyzed using SPSS with ANOVA followed by Post Hoc tests. The results showed that all treatment groups exhibited significant differences in aphrodisiac activity, with the highest frequency observed in the 1:1 combination of bitter melon extract (980 mg/kg BW) and garlic extract (150 mg/kg BW) compared to other effervescent tablet formulations.